High yield and efficiency: cultivar selection to improve potato nitrogen use efficiency - Carruthers, Laura C.; Congreves, Kate A. (Frontiers in Agronomy, 2025)
Optimizing nitrogen use efficiency (NUE) of crops is critical to maintain yields and profits while minimizing environmental damage from excessive fertilization and nitrogen (N) losses. Potato (Solanum tuberosum L.) typically requires high N rates to support yield, but low NUE risks N losses with cascading environmental and financial consequences. Identifying potato cultivars with improved NUE may reduce fertilizer needs and lower the risk of N loss. However, little research has focused on identifying such cultivars, especially on the Canadian Prairies. We conducted a field study encompassing five site-years in Saskatchewan to compare six seed potato cultivars (Clearwater Russet, Dark Red Norland, Milva, Poppy, Russet Burbank, and Sangre) for NUE traits, under N fertilizer rates ranging from 0 to 200 kg N ha-1. Total yield, tuber N content, N balance intensity (NBI) and tuber N uptake efficiency (NUpE) were quantified as measures of NUE. Cultivar significantly influenced all metrics (p < 0.05), whereas fertilizer or the two-way interaction did not. Cultivar yield varied by more than 45%, highlighting substantial productivity differences among cultivars. Dark Red Norland, Sangre and Poppy also showed 22.5-33.2% higher NUE than other cultivars. Our findings support the need for improved predictions of soil mineralizable N supply, as reducing or forgoing N fertilization improves potato NUE when indigenous soil N meets crop demand. Our results suggest that when yield is not limited by soil N, NUE is largely driven by the ability of the plant to produce greater yield. This research demonstrates specific cultivars deliver high yields and improved NUE, allowing for improved N balance in potato production systems.